Optimal Annuity Risk Management - Koijen, Ralph S. J.; Nijman, Theo E.; Werker, Bas J. M. (Review of Finance, 2011)
Abstract This paper studies the life-cycle consumption and portfolio choice problem taking account of annuity risk at retirement. The study allows for government-provided annuity income. Optimally, households allocate retirement wealth to nominal, inflation-linked and variable annuities, and condition this choice on the state of the economy. The case in which there are limitations in the types of annuities that are available is also considered and the costs of annuity market incompleteness are quantified. Subsequently, the paper determines how investors optimally anticipate annuitization before retirement. The conclusion is that ignoring annuity risk before and at retirement can be economically costly.